Peripheral Effects of FAAH Deficiency on Fuel and Energy Homeostasis: Role of Dysregulated Lysine Acetylation - Vaitheesvaran, Bhavapriya (Public Library of Science, 2012)
BACKGROUND: FAAH (fatty acid amide hydrolase), primarily expressed in the liver, hydrolyzes the endocannabinoids fatty acid ethanolamides (FAA). Human FAAH gene mutations are associated with increased body weight and obesity. In our present study, using targeted metabolite and lipid profiling, and new global acetylome profiling methodologies, we examined the role of the liver on fuel and energy homeostasis in whole body FAAH(−/−) mice. METHODOLOGY/PRINCIPAL FINDINGS: FAAH(−/−) mice exhibit altered energy homeostasis demonstrated by decreased oxygen consumption (Indirect calorimetry). FAAH(−/−) mice are hyperinsulinemic and have adipose, skeletal and hepatic insulin resistance as indicated by stable isotope phenotyping (SIPHEN). Fed state skeletal muscle and liver triglyceride levels was increased 2–3 fold, while glycogen was decreased 42% and 57% respectively. Hepatic cholesterol synthesis was decreased 22% in FAAH(−/−) mice. Dysregulated hepatic FAAH(−/−) lysine acetylation was consistent with their metabolite profiling. Fasted to fed increases in hepatic FAAH(−/−) acetyl-CoA (85%, p<0.01) corresponded to similar increases in citrate levels (45%). Altered FAAH(−/−) mitochondrial malate dehydrogenase (MDH2) acetylation, which can affect the malate aspartate shuttle, was consistent with our observation of a 25% decrease in fed malate and aspartate levels. Decreased fasted but not fed dihydroxyacetone-P and glycerol-3-P levels in FAAH(−/−) mice was consistent with a compensating contribution from decreased acetylation of fed FAAH(−/−) aldolase B. Fed FAAH(−/−) alcohol dehydrogenase (ADH) acetylation was also decreased. CONCLUSIONS/SIGNIFICANCE: Whole body FAAH deletion contributes to a pre-diabetic phenotype by mechanisms resulting in impairment of hepatic glucose and lipid metabolism. FAAH(−/−) mice had altered hepatic lysine acetylation, the pattern sharing similarities with acetylation changes reported with chronic alcohol treatment. Dysregulated hepatic lysine acetylation seen with impaired FAA hydrolysis could support the liver's role in fostering the pre-diabetic state, and may reflect part of the mechanism underlying the hepatic effects of endocannabinoids in alcoholic liver disease mouse models.